Chitosan and modified chitosan for essential oils encapsulation: a review - Serina Amka Putri; Azlan Kamari; Mierta Dwangga; Sunardi Sunardi (Konversi, 2026)
This review discusses the role of chitosan and modified chitosan as encapsulation matrices for essential oils (EOs) to overcome the limitations of volatility, hydrophobicity, and instability that have historically hindered the application of EOs in the food, pharmaceutical, cosmetic, and agricultural fields. Thru a literature review, this article examines the composition and extraction methods of EO; the principles, wall materials, and encapsulation techniques; and chitosan modification strategies ranging from cross-linking (e.g., sodium tripolyphosphate/TPP, glutaraldehyde), grafting functional groups, sulfation, to composite formation with other polymers (alginate, pectin, gelatin, cellulose, PVA). Generally, chitosan enhances oxidative stability, protects against light/oxygen/heat, improves solubility and bioavailability, and enables controlled release while providing antimicrobial and antioxidant properties that synergize with EO. Performance evidence is demonstrated by high encapsulation efficiency (often >80–90%) and nano particle size (<100 nm) in a number of formulations. For example, chitosan–TPP/alginate nanoparticles for rosemary oil achieved >98% efficiency with a size <100 nm, while oregano oil in chitosan–TPP nanoparticles reached 92.90%. Highlighted applications include active food preservatives and smart packaging, drug/topical delivery, biopesticides and fungal control, and the inhibition of resistant pathogens (e.g., Klebsiella pneumoniae). Nevertheless, the challenges toward commercialization still include process scale, cost, material standardization, long-term release control, and safety evaluation. Overall, chitosan and its derivatives emerge as versatile and promising encapsulating agents for enhancing the effectiveness, stability, and added value of essential oils across various sectors.